The Use of Weightlifting Pulling Movements in Sport - Weightlifting Training/Summary - Stone, Mi.; Gattone, M.; Stone, Ma.; Schilling, B.; Pierce, K.; Byrd, R. (coachesinfo.com)
While we realise that in most sports the purpose of training is not to produce weightlifters we do believe that it is reasonable to consider, briefly, their basic training programmes. Weightlifting training can offer several techniques, methods and ideas not typically inherent in many other sports training programmes. Training programmes for weightlifters generally follow a periodised or variation method. On a mesocycle level training is generally carried out in two stages; general preparation and competition. General preparation may contain a strength endurance phase and a basic strength phase, while competition emphasises power and speed and has a brief taper before an important meet. Typical exercises would include: - Various types of squats such as back and front squats weighted and un-weighted jumps. - Various types of presses. - Jerks. - Various types of pulling movements, which make up the majority of the different types of exercises used by most weightlifters. - Mid-section and body stability exercises. Training Effects Training effects from this type of programme can include: - Enhance metabolism. - Body composition alterations. - Specifically enhanced force-time characteristics - Enhanced power output. As previously discussed power is likely the most important characteristic to develop for the majority of sports. The explosive training used by weightlifters, particularly the pulling movements, should contribute to increased whole body movement power. Two recent studies comparing the power output of different athletes support this concept. McBride et al. (1999) studied elite Australian weightlifters, powerlifters, sprinters and untrained subjects. Power output normalised for body mass was assessed through weighted jumping. Jumps were performed at 0, 20 and 40 kg and at 30, 60 and 90 % of their 1RM squat from a 900 knee angle. The results showed that the weightlifters produced the greatest power output at any load Controlling for maximum strength differences and using weighted jumping Stone and Stone (2001) found weightlifters to produce higher power outputs than powerlifter/heavy weight trainers, wrestlers or an untrained group at any percentage of the maximum 1 RM parallel squat (Figure 21). These data (McBride et al. 1999, Stone and Stone 2001) indicate that weightlifting training can be advantageous for whole body power production. There is no reason to believe that these results would not be advantageous to a variety of sports. Thus considering aspects of the training of weightlifters and using these aspects in the training of athletes in other sports is quite reasonable. In summary it may be stated that pulling movements can provide physiological and biomechanical advantages that can enhance the performance in a variety of sports. Primary considerations in the enhancement process is using appropriate technique and providing reasonable overloads.